1974
DOI: 10.1042/bj1430039
|View full text |Cite
|
Sign up to set email alerts
|

Lipid and basic protein interaction in myelin

Abstract: 1. Purified myelin labelled with [(3)H]myo-inositol or [1-(14)C]acetate was incubated with trypsin or acetylated trypsin at 37 degrees C, pH8.0 for 30min. 2. After incubation and centrifugation analysis of the myelin pellet showed marked digestion of basic protein on polyacrylamide-gel electrophoresis. Proteolipid and Wolfgram proteins remained unchanged. 3. A loss of 15% of total protein and loss of all classes of lipids was also found. Most significant lipid losses were phosphoinositides, phosphatidylserine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
16
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 50 publications
4
16
0
Order By: Relevance
“…Methionine residues were successfully regenerated by treatment with thioglycollic acid. The specific interaction of the myelin basic protein with acidic lipids reported by Palmer & Dawson (1969) and Banik & Davison (1974) has been confirmed in the present study. The observation that neither peptide fragment showed any interaction with complex lipids such as cerebroside, sphingomyelin and phosphatidylcholine is not surprising, since this is also the case for the intact basic protein ; the present work).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Methionine residues were successfully regenerated by treatment with thioglycollic acid. The specific interaction of the myelin basic protein with acidic lipids reported by Palmer & Dawson (1969) and Banik & Davison (1974) has been confirmed in the present study. The observation that neither peptide fragment showed any interaction with complex lipids such as cerebroside, sphingomyelin and phosphatidylcholine is not surprising, since this is also the case for the intact basic protein ; the present work).…”
Section: Resultssupporting
confidence: 89%
“…For a two-phase system to study lipid interaction with protein (Palmer & Dawson, 1969;Banik & Davison, 1974) samples of lipid (up to 400ug) were evaporated under N2 in stoppered test tubes. Chloroform/methanol (2:1, v/v; 1.Oml) was added to each tube, followed by 0.25 ml of lOmM-Tris/HCI buffer, pH7.0, which contained about 100,ug of protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Steck et al (1976) reported that this binding could be reduced by acylating a number of the lysyl residues on the protein, presumably by reducing its net positive charge. Evidence that portions of the basic protein could extend into a lipid bilayer also has been presented (Boggs & Moscarello, 1978). These and other studies Demel et al, 1973;Smith, 1977a) support the notion that MBP can interact with both the hydrophobic and hydrophilic portions of lipid bilayers.…”
mentioning
confidence: 53%
“…Basic protein in situ in purified myelin is easily hydrolysed by acetylated trypsin (Wood et al, 1974;Banik & Davison, 1974), and purified basic protein is hydrolysed by purified brain acid proteinase (Einstein et al, 1968), Pronase, and elastase (M. E. Smith, unpublished work). When associated with myelin lipid, basic protein may be partially protected from the activity of proteolytic enzymes (London & Vossenberg, 1973).…”
Section: Discussionmentioning
confidence: 99%